2019
DOI: 10.1093/cid/ciz1071
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Meta-analysis of Rifampicin Exposure and Mortality in Indonesian Tuberculous Meningitis Trials

Abstract: Background Intensified antimicrobial treatment with higher rifampicin doses may improve outcome of tuberculous meningitis, but the desirable exposure and necessary dose are unknown. Our objective was to characterize the relationship between rifampicin exposures and mortality in order to identify optimal dosing for tuberculous meningitis. Methods An individual patient meta-analysis was performed on data from three Indonesian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 42 publications
2
64
2
Order By: Relevance
“…EC99) with PTA of 91% (22). Another study investigating Indonesian adults with TBM showed that rifampicin 40 mg/kg/day would be required to reach a PTA around 95% (23). Children studied here required a higher dose of rifampicin compared to adults due to lower plasma rifampicin exposures, resulting from a nonlinear relationship between body weight and drug elimination processes (46).…”
Section: Discussionmentioning
confidence: 80%
“…EC99) with PTA of 91% (22). Another study investigating Indonesian adults with TBM showed that rifampicin 40 mg/kg/day would be required to reach a PTA around 95% (23). Children studied here required a higher dose of rifampicin compared to adults due to lower plasma rifampicin exposures, resulting from a nonlinear relationship between body weight and drug elimination processes (46).…”
Section: Discussionmentioning
confidence: 80%
“…The PK analysis included 133 individuals and 1150 rifampicin concentrations (170 from CSF) and the survival analysis included 148 individuals of whom 58 died and 15 dropped out. Higher individual plasma rifampicin exposures (AUC 0-24h ), lower age and higher baseline Glasgow coma scale (GCS) scores reduced the hazard of death 38 . Figure 2 shows how simulations predicted an increase in 6-month survival from approximately 50% to approximately 70% upon increasing the oral rifampicin dose from 10 to 30 mg/kg, and predicted that even higher doses would further improve survival 38 .…”
Section: Situation Of Equipoisementioning
confidence: 99%
“…Higher individual plasma rifampicin exposures (AUC 0-24h ), lower age and higher baseline Glasgow coma scale (GCS) scores reduced the hazard of death 38 . Figure 2 shows how simulations predicted an increase in 6-month survival from approximately 50% to approximately 70% upon increasing the oral rifampicin dose from 10 to 30 mg/kg, and predicted that even higher doses would further improve survival 38 . Based on this analysis it was concluded that higher rifampicin exposures early during treatment substantially decrease the risk of death and that optimal dose of rifampicin in treatment of TBM should be further investigated in phase III trials.…”
Section: Situation Of Equipoisementioning
confidence: 99%
See 2 more Smart Citations